Stability of Tenogenic Secretomes Optical Density, Colour, Weight, TGF-β Concentration and Bacterial Growth after 30-Day Storage under Room оr Refrigerator Temperature - Aziz, Mukhlis; Soesilawati, Pratiwi; Lestari, Pudji; Suroto, Heri (Scripta Medica, 2025)
Background/Aim: The effectiveness and efficiency of tenogenic secretomes products are crucial to assess. Storage conditions affect both the distribution process and the stability of the tenogenic secretomes and their components. This study aimed to examine how different storage temperatures impact the stability of tenogenic secretomes chemically, physically and biologically.Methods: This in vitro experimental, comparative study was conducted in a laboratory setting. The effect of room temperature (R) at 20-25 °C was compared with a refrigerator (K) at 4 °C on tenogenic secretome stability over 30 days. The sample size was 24 liquid tenogenic secretomes determined using the Federer Formula (1963). The samples were divided into four groups: (R1, K1) for day-1 evaluation and (R30, K30) for day-30 evaluation. The parameters used in this study were physical (optical density (OD); weight differences (Δ weight) and colour changes); chemical (transforming growth factor beta (TGF-β) concentration); and biological (bacterial growth) stability. The main outcome measures were TGF-β concentration, colour, weight differences, optical density changes and bacterial growth. Results: There were no significant differences between each parameter evaluation in the R1-K1 group ((OD, p-value = 0.729); (TGF-β, p-value = 0.656); (Δ weight, p-value = 0.262)) or R30-K30 group ((OD, p-value = 0.505); (TGF-β p-value = 0.182); (Δ weight, p-value = 0.214)). There was no significant correlation between the storage temperature and bacterial growth in either the R1-K1 group (p-value = 0.439) or R30-K30 group (p-value = 0.439). The R30 group samples, however, displayed more noticeable colour changes compared to the initial colour and the K30 group.Conclusion: The OD, TGF-β, weight, colour and bacterial growth were not significantly affected at either fridge or room temperature. The components of the tenogenic secretome remained stable after 30 days of storage without experiencing substantial deterioration despite the temperature condition.